2015
DOI: 10.5705/ss.2013.242
|View full text |Cite
|
Sign up to set email alerts
|

A non parametric approach for calibration with functional data

Abstract: International audienceA new nonparametric approach for statistical calibration with functional data is studied. The practical motivation comes from calibration problems in chemometrics in which a scalar random variable Y needs to be predicted from a functional random variable X. The proposed predictor takes the form of a weighted average of the observed values of Y in the training data set, where the weights are determined by the conditional probability density of X given Y. This functional density, which repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The role of nonclassical isomers in empty fullerene growth has been modeled, [64] and one-heptagon isomers have been proposed to contribute to the high relative abundance of I h -symmetrical C 60 , since this isomer can be formed by C 2 insertion into the most stable one-heptagon isomer of C 58 . [64] Theoretical study showed that nonclassical isomers of C 68 containing a heptagon play a key role in the formation of fullerene C 70 and fullerene derivative C 68 Cl 6 . [65] In the map shown in Figure 2, the cage C 80 :31924, the parent of many EMFs, is similarly related by C 2 insertion to the one-heptagon isomer C 1h 78 :185809.…”
Section: Full Papermentioning
confidence: 99%
“…The role of nonclassical isomers in empty fullerene growth has been modeled, [64] and one-heptagon isomers have been proposed to contribute to the high relative abundance of I h -symmetrical C 60 , since this isomer can be formed by C 2 insertion into the most stable one-heptagon isomer of C 58 . [64] Theoretical study showed that nonclassical isomers of C 68 containing a heptagon play a key role in the formation of fullerene C 70 and fullerene derivative C 68 Cl 6 . [65] In the map shown in Figure 2, the cage C 80 :31924, the parent of many EMFs, is similarly related by C 2 insertion to the one-heptagon isomer C 1h 78 :185809.…”
Section: Full Papermentioning
confidence: 99%
“…The 'usual', HPV-related, pigmented VIN (case 4) showed well-demarcated borders and parallel pigmented dots, which may also be observed in pigmented BD (aligned pigmented globules also representing a dermoscopic feature of labial lentigo simplex). [12][13][14][15] However, the presence of a cerebriform pattern, detected by Ronger-Savle et al on pigmented VIN, 8 suggested the diagnosis of VIN, which was confirmed by histopathology.…”
mentioning
confidence: 99%
“…Several works are related to the importance of free hand sketching in engineering design [3,11,12], or to the development of workshops or whole courses for the improving of spatial visualization abilities through the use of sketches and CAD modeling software [13][14][15][16]. In different works, there are also presented multimedia or webbased tools, properly developed, aimed at improving students' visualization or sketching abilities [17][18][19][20][21][22][23]. On the other hand, there are a few works focused on teaching and helping students to learn how to dimension an object or a mechanical workpiece.…”
Section: Overview On Engineering Drawing Learning Toolsmentioning
confidence: 99%